IMMU-20. HYDROGEL-CXCL9 VACCINE RESULTS IN MRNA DELIVERY TO DENDRITIC CELLS AND POTENT ANTI-TUMOR RESPONSES IN GBM. (12th November 2021) - Dastmalchi, Farhad; Karachi, Aida; Mehkri, Yusuf; O'Malley, Ashley; Subramaniam, Vignesh; Angelini, Thomas; Mitchell, Duane; Rahman, Maryam
Abstract: INTRODUCTION: Our group and others have shown mRNA-vaccines have significant anti-tumor efficacy in the treatment of brain tumors and are currently being tested in first-in-human trials. To further enhance mRNA delivery, a hydrogel platform was developed with the addition of CXCL9 to promote immune cell trafficking. METHODS: We generated the vaccine by utilizing a hydrogel platform. CXCL9 and Nano-mRNA were loaded into the hydrogel. In vitro recruitment of DCs and NK was evaluated by fluorescence microscopy. In vivo recruitment of immune cells was analyzed by flowcytometry after collecting the fat pad, spleen, and tumor samples from KR158b-luc and Gl261-gp100 tumor-bearing animals 3, 5 and 10 days after vaccine delivery. The efficacy of the vaccine was evaluated by measuring overall survival, and tumor growth was measured by IVIS live-imaging. RESULTS: Dendritic cells(DCs) and natural killer(NK) cells were able to efficiently migrate within the hydrogel-CXCL9 platform and uptake and express mRNA in vivo. In vitro, the hydrogel-CXCL9 was combined with nanoparticles loaded with total tumor RNA, and the vaccine was delivered to KR-158-luc and GL261-gp100 tumor-bearing animals via mammary fat pad SQ injection. Flow cytometry of the fat pad and draining lymph nodes demonstrated showed significant recruitment of endogenous DCs including inflammatory-DC(P= 0.0035), conventional-DC1(P= 0.0076), pDC(P=0.0028), NK(p= 0.0025 compared to the control group. In two different tumor models, a single dose of the vaccine resulted in significant survival benefits compared to control animals (n=10, P< 0.0001). SQ injection was superior to intracranial injection of the vaccine. Vaccinated animals showed an increased number of antigen-specific CD8 T cells in spleen(P= 0.0001) and tumor-microenvironment(P= 0.0070). CONCLUSION: The hydrogel-CXCL9 platform results in efficient delivery of mRNA loaded nanoparticles to endogenous DCs and also causes an upregulation of NK cells with resultant improved survival in murine GBM models including the highly resistant KR158 model with a single dose. Further studies are ongoing.